Visual Identity Angkringan Mintuo Talawi - Lia Gusrianti; Hendra Afriwan (Jurnal Kajian dan Penelitian Umum, 2023)
Angkringan Mintuo is an angkringan whose identity is still in the form of a simple signboard that just says Angkringan Mintuo. This is a problem so that it does not yet have a visual identity in the form of a logo that can increase attractiveness and represent the image and characteristics of this angkringan. The purpose of making this angkringan visual identity is to have its own characteristics for this angkringan so that it can be easily recognized by the target audience. The creation of this visual identity is in the form of a brand, logotype and tagline. Glass Box is a design method that is being used. Glass Box is a design that is made logically and rationally using information from data collection, interviews, observation, and documentation. The analytical method used is called 5W+1H analysis (what, where, when, why, who, how). The design of the angkringan brand will be featured in the manual book as the main media and supporting media, namely banners, stickers, t-shirts, aprons, packaging, email, business cards, etc. which aim to strengthen the main media.